An autopsy case of granulomatous amebic encephalitis caused by Balamuthia mandrillaris involving prior amebic dermatitis. Issue 3 (14th February 2022) - Maehara, Tatsuro; Mizuno, Tetsushi; Tokoro, Masaharu; Hara, Tatsuru; Tomita, Yui; Makioka, Kouki; Motegi, Sei‐Ichiro; Yamazaki, Ayako; Matsumura, Nozomi; Nobusawa, Sumihito; Yokoo, Hideaki
Abstract : An 82‐year‐old man, who was healthy and had worked as a farmer, experienced worsening neurological symptoms over a seven‐month period, which eventually caused his death. Multiple fluctuating brain lesions were detected radiographically. Clinically, sarcoidosis was ranked high among the differential diagnoses because of the presence of skin lesions showing granulomatous inflammation, confirmed by biopsy. The patient's cerebrospinal fluid was also examined, but no definitive diagnosis was made while he was alive. An autopsy revealed multiple granulomatous amebic encephalitis lesions in the brain. Genetic and immunohistochemical analyses identified Balamuthia ( B. ) mandrillaris, a free‐living ameba, which resides in soil and fresh water, as the causative organism. A retrospective examination revealed B. mandrillaris in the biopsied skin as well as cerebrospinal fluid, strongly suggesting that the ameba had spread into the brain percutaneously. Few studies have detailed the cutaneous pathology of B. mandrillaris infections. In general, granulomatous amebic encephalitis is extremely difficult to diagnose without autopsy, but the present case provides a clue that could allow similar cases to be diagnosed earlier; that is, the presence of skin lesions.